Contrast-enhanced ultrasound in monitoring the efficacy of a bradykinin receptor 2 antagonist in painful knee osteoarthritis compared with MRI. Issue 1 (28th March 2008) - Song, I H; Althoff, C E; Hermann, K G; Scheel, A K; Knetsch, T; Burmester, G R; Backhaus, M
Abstract : Objectives: To evaluate contrast-enhanced ultrasound (CE-US) as a monitoring tool to assess hypervascularisation of synovial processes in knee osteoarthritis (OA) treated with intra-articular injections of the bradykinin-receptor 2 antagonist icatibant compared to contrast-enhanced magnetic resonance imaging (CE-MRI). Patients and methods: In a randomised, double-blind, placebo-controlled trial, 41 patients with painful knee OA underwent US (12.5 MHz for B-mode and 3–8 MHz for CE-US), and 36 of the patients underwent additional MRI (0.2T) at baseline and after 3 injections of the study drug (after a mean of 22.2 days). A total of 15 patients received placebo (group A), 12 patients 500 μg icatibant (group B) and 14 patients 2000 μg icatibant (group C). Pain and the synovial process (B-mode, power Doppler US (PD-US), CE-US, CE-MRI) were assessed at both time points. Results: At baseline, the placebo group showed more activity in terms of effusion in the superior and lateral recess in ultrasound as well as in PD-US in the lateral recess. Pain improved significantly in all subgroups. Effect sizes were 0.43 (pain at rest) and 0.52 (pain during activity) in group B vs 0.48 and 1.11 in group C. There was no change of US and MRI parameters. We found moderate to good correlation (r) and kappa values (κ) for effusion in the superior recess (r = 0.591, k = 0.453), effusion in the lateral recess (r = 0.304, k = 0.440) and contrast enhancement (r = 0.601, k = 0.242) between US and MRI. Conclusions: Our results show that CE-US and CE-MRI have good agreement in assessing inflammatory changes in knee OA. For the 41 patients with OA, an analgesic effect of icatibant could clearly be shown, especially for pain during activity in the high dose icatibant group. However, we could not find an anti-inflammatory effect of icatibant by CE-US compared to CE-MRI.